2019
DOI: 10.17816/maj19237-42
|View full text |Cite
|
Sign up to set email alerts
|

The specific activity of proteins involved in iron metabolism depends on compensation of type 2 diabetes mellitus

Abstract: Objective. We aimed to analyze the alterations of activity of iron metabolism members i.e. ceruloplasmin (Cp) and transferrin (Tf), in relation to the percentage of glycated hemoglobin. The latter is one of biochemical criteria of chronic hyperglycemia compensation in case of type 2 diabetes mellitus. Materials and methods. Concentration and activity of Cp and Tf, concentration of iron, copper and lipoprotein cholesterol were measured by biochemical methods in blood serum samples obtained from healthy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…also, hyperglycemia increases the concentrations of Cp and a drop in its sp. act 28 . A study which was first to research the relationship of Cp activity with VHD found that the patients had significantly elevated Cp ferroxidase activity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…also, hyperglycemia increases the concentrations of Cp and a drop in its sp. act 28 . A study which was first to research the relationship of Cp activity with VHD found that the patients had significantly elevated Cp ferroxidase activity 29 .…”
Section: Discussionmentioning
confidence: 99%